The Influence of Cross-Divisional Communication and Career Development on Employee Morale at PT. PLN (Persero) Ampera Branch - Ardiansyah, Rama Pratama; Aliya, Sabeli (Sinergi International Journal of Management and Business, 2024)
This study seeks to evaluate the impact of cross-divisional communication and career development on employee morale at PT. PLN (Persero) Ampera Branch. Employing a population-based approach with total sampling techniques, data were gathered through questionnaires distributed to 113 respondents. The study uses a quantitative methodology with an associative causal explanation. Data analysis includes assessments of data quality, classical assumption testing, multiple linear regression analysis, evaluation of the coefficient of determination, and hypothesis testing. The findings indicate a positive influence of cross-divisional communication and career development on employee morale at PT. PLN (Persero) Ampera Branch, both individually and collectively.